Strategies to Reduce Pathological Fear in Mathematics among Secondary School Students in Adamawa State, Nigeria - Yahya, Anaf Sulienam; Fasasi, K M. (JPAIR Multidisciplinary Research, 2012)
The purpose of this study is to identify causes of pathological fear in Mathematics among secondary school students in Adamawa State, Nigeria. The study also examines strategies that could be adopted to reduce pathological fear in Mathematics among students. Three research questions and a hypothesis tested at a = 0.05 level of significant were formulated to guide the study. A research questionnaire on Pathological Fear in Mathematics Questionnaire (PFMATQ) was used in collecting data from 250 senior secondary school students. They were selected by stratified random sampling technique from five educational zones in Adamawa State. Mean, standard deviation and t-test were used to analyses the data generated. The study reveals that causes of pathological fear in Mathematics among others include: parental indoctrination that Mathematics is difficult, the Mathematics teacher factor and the abstract nature of Mathematics. Strategies that could be adopted to reduce pathological fear in Mathematics among others include; the use of mathematical games; uses of heuristic method of teaching and use of relevant set induction techniques. It is recommended that parents should stop indoctrinating their children that Mathematics is difficult; they should keep away their unpleasant experiences about Mathematics and present favorable ones to encourage them to develop interest in Mathematics. Recommendations were outlined.